FPGA Programming for Beginners - Bruno, Frank (Packt Publishing, 2021)
Get started with FPGA programming using SystemVerilog, and develop real-world skills by building projects, including a calculator and a keyboard Key Features Explore different FPGA usage methods and the FPGA tool flow Learn how to design, test, and implement hardware circuits using SystemVerilog Build real-world FPGA projects such as a calculator and a keyboard using FPGA resources Book Description Field Programmable Gate Arrays (FPGAs) have now become a core part of most modern electronic and computer systems. However, to implement your ideas in the real world, you need to get your head around the FPGA architecture, its toolset, and critical design considerations. FPGA Programming for Beginners will help you bring your ideas to life by guiding you through the entire process of programming FPGAs and designing hardware circuits using SystemVerilog. The book will introduce you to the FPGA and Xilinx architectures and show you how to work on your first project, which includes toggling an LED. You'll then cover SystemVerilog RTL designs and their implementations. Next, you'll get to grips with using the combinational Boolean logic design and work on several projects, such as creating a calculator and updating it using FPGA resources. Later, the book will take you through the advanced concepts of AXI and serial interfaces and show you how to create a keyboard using PS/2. Finally, you'll be able to consolidate all the projects in the book to create a unified output using a Video Graphics Array (VGA) controller that you'll design. By the end of this SystemVerilog FPGA book, you'll have learned how to work with FPGA systems and be able to design hardware circuits and boards using SystemVerilog programming. What you will learn Understand the FPGA architecture and its implementation Get to grips with writing SystemVerilog RTL Make FPGA projects using SystemVerilog programming Work with computer math basics, parallelism, and pipelining Explore the advanced topics of AXI and serial interfaces Discover how you can implement a VGA interface in your projects Who this book is for This FPGA design book is for embedded system developers, engineers, and programmers who want to learn FPGA and SystemVerilog programming from scratch. FPGA designers looking to gain hands-on experience in working on real-world projects will also find this book useful.